2022
DOI: 10.35134/ekobistek.v11i3.364
|View full text |Cite
|
Sign up to set email alerts
|

Jumlah Wisatawan, Jumlah Hotel, dan Jumlah Objek Wisata terhadap Pendapatan Asli Daerah Kabupaten Tuban

Abstract: Sektor pariwisata adalah salah satu sumber penerimaan daerah yang menjadi penyumbang pendapatan asli daerah melalui pajak daerah dan retribusi daerah. Agar dapat meningkatkan pendapatan asli daerah di kabupaten Tuban, maka diharapkan pemerintah dan masyarakat sekitar diupayakan untuk terus mengelola dan merawat sumberdaya alam untuk dijadikan sebagai tempat wisata agar dapat menarik pengunjung untuk terus berwisata di daerah tersebut. Penelitian ini dilakukan di kabupaten Tuban pada tahun 2006-2020 seama perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
1
1
0
1
Order By: Relevance
“…On the other hand, this research concurs with studies by Sari & Dewi (2023) and Nurainina & Asmara (2022), which found that the number of hotels positively and significantly affects PAD. However, Asmisari et al (2021) reported that the number of hotels does not significantly influence PAD in the tourism sub-sector.…”
Section: The Random Effect Model (Rem)supporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, this research concurs with studies by Sari & Dewi (2023) and Nurainina & Asmara (2022), which found that the number of hotels positively and significantly affects PAD. However, Asmisari et al (2021) reported that the number of hotels does not significantly influence PAD in the tourism sub-sector.…”
Section: The Random Effect Model (Rem)supporting
confidence: 92%
“…Utilizing secondary data from various sources including the Central Bureau of Statistics (BPS) and literature sources, they employed multiple linear regression analysis. Their findings revealed that collectively, the number of tourist visits, tourist attractions, and Secondly,Nurainina and Asmara (2022) investigated the influence of the number of tourists, hotels, and tourist attractions on PAD in Tuban Regency spanning from 2006 to 2020.…”
mentioning
confidence: 99%
“…b. Hausman Test: untuk memilih antara Fixed Effect Model (FEM) atau Random Effect Model (REM)Sebelum dilakukan regresi, maka dilakukan Uji Asumsi Klasik berupa Uji Multikolinearitas yaitu uji untuk melihat mengetahui dalam regresi terdapat adanya korelasi dalam model regresi. Kemudian Uji Heterokedasititas yaitu untuk melihat ketidaksamaan varian erorr semua pengamatan variabel independent dalam model regresi[10]. Selanjutnya untuk uji hipothesis menggunakan Uji Statistik.3.…”
unclassified